The practice of village branding and marginalisation in Mojokerto, Indonesia - Hidayat, Endik; Susilo, Daniel; Baihaqi, Aufa Izzudin (Jurnal Studi Komunikasi, 2022)
The background of this research is the phenomenon of villages that fail in branding and developing a positive image that causes marginalisation and stigma. The two research locations are the Sumberglagah ‘Leprosy Village’ in Tangjungkenongo and the ‘Duck Village’ in Modopuro. This study intended to answer two questions: how does it apply the place branding concept in the village scope? And more specifically, how do the village elites respond to these stigmas and discriminatory treatment the villagers receive? We used qualitative methods through interviews and questionnaires to answer these questions. This study found that the Tanjungkenongo village is known as the “Leprosy Village,” and one of the Sub-Villages in Sumberglagah is called the “Beggar Village.” On the other hand, the Modopuro village is known as the “Duck Village,” and Sememi’s Sub-Village is known as the “Chicken Intestine Waste Village.” As a response, the Tanjungkenongo Village elites tend to accept these outsiders’ perceptions towards their village. Meanwhile, the Modopuro Village Elites were divided into two groups. The elites who own related industries (duck farming, poultry slaughter, chicken intestine chips) feel comfortable with this image. In contrast, the elites who have no direct interest in the industries directly reject those outsiders’ views.